گابرئیل گارسیا مارکیز کے افسانوں کے اُردو تراجم: Urdu Translations of the Short Stories of Gabriel García Márquez (Al-Aasar, 2025)
Latin American writer Gabriel Garcia Marquez’s magical realism in fiction enjoys recognition across the globe. His work focuses on political, socio-economic and cultural challenges of a postcolonial society. His fiction, in terms of technique and subject matter, is a representative of postcolonial discourse. The study, presents an historical account of Urdu translations of Marquez’s short stories. The study also takes into account the literary values of Urdu translations. For example, an attempt has been made to compare and contrast various Urdu translations of Marquez’s work keeping in view of their source texts. The study concludes that most of the Urdu translations of Marquez’s work, on their sub-conscious level, seems to have benefitted from modern translation techniques, based on linguistic theories, to draw a formal and communicative equivalence with the source text.